The global regulatory framework for the commercialization of nutrient enriched biofortified foods - Mitra-Ganguli, Tora; Pfeiffer, Wolfgang H.; Walton, Jenny (Wiley, 2022)
Nutrient enriched crops (NECs) were developed through biofortification as a tool to reach the world's most vulnerable. The delivery model developed by HarvestPlus for the scaling of NECs relies on commercial demand from food businesses and consumers, coupled with the ability to promote and market foods that comply with legislation. This review of standards, regulations, and laws across the value chain in 20 countries demonstrates that existing provisions for food labeling are sufficient to carry out sales and marketing of foods made from conventionally bred NECs. The term biofortification is not necessary to create demand and, potentially, is counterproductive. Promoting the natural source of vitamins and minerals and relevant nutrition claims is the most effective and simple way to signpost healthier products to consumers. Until 2021, it was not possible to distinguish NECs at the grain level from the market standard. The development of a globally relevant Publicly Available Specification allows traders to demand grains that offer a substantial increase in zinc, iron, or vitamin A. Addressing this gap at the grain level ensures that standards and regulations are available end-to-end in the food supply chain providing the enabling environment for the rapid scale of NECs.